A study of the correlation between stroke and gut microbiota over the last 20years: a bibliometric analysis - Han, Shengnan; Cai, Longhui; Chen, Peipei; Kuang, Weihong (Frontiers in Microbiology, 2023)
Purpose: This study intends to uncover a more thorough knowledge structure, research hotspots, and future trends in the field by presenting an overview of the relationship between stroke and gut microbiota in the past two decades. Method: Studies on stroke and gut microbiota correlations published between 1st January 2002 and 31st December 2021 were retrieved from the Web of Science Core Collection and then visualised and scientometrically analysed using CiteSpace V. Results: A total of 660 papers were included in the study, among which the USA, the UK, and Germany were the leading research centres. Cleveland Clinic, Southern Medical University, and Chinese Academy of Science were the top three institutions. The NATURE was the most frequently co-cited journal. STANLEY L HAZEN was the most published author, and Tang WHW was the most cited one. The co-occurrence analysis revealed eight clusters (i.e., brain-gut microbiota axis, fecal microbiome transplantation, gut microbiota, hypertension, TMAO, ischemic stroke, neuroinflammation, atopobiosis). "gut microbiota," "Escherichia coli," "cardiovascular disease," "risk," "disease," "ischemic stroke," "stroke," "metabolism," "inflammation," and "phosphatidylcholine" were the most recent keyword explosions. Conclusions: Findings suggest that in the next ten years, the number of publications produced annually may increase significantly. Future research trends tend to concentrate on the mechanisms of stroke and gut microbiota, with the inflammation and immunological mechanisms, TMAO, and faecal transplantation as hotspots. And the relationship between these mechanisms and a particular cardiovascular illness may also be a future research trend.